ETHICAL DISSONANCE, ETHICAL DISJUNCTURE, AND THE AUTONOMOUS SPHERES. Issue 4 (1st February 2022) - Shingleton, Bradley
Abstract: The contemporary ethical landscape appears to many to be marked by a plurality of normative regions. The values and standards of one region may contrast and conflict with those of other regions, creating a sense of dissonance and discontinuity for the individual agent. This article explores how the phenomenon of such dissonance might be conceptualized. It considers the attempts of two thinkers who, following on Weber's notion of autonomous spheres, give a theoretical account of a pluralized ethical environment in terms of distinct, autonomous zones that reflect distinctive assumptions about rationality and action. While such Weber‐inspired theories are compelling in some respects, they have the potential of overemphasizing the autonomy of the various regions. An alternative idea of ethical sectors, rather than orders, seeks to avoid this problem by positing a more porous, less delimited ethical landscape, one that allows for a sense of ethical identity that an agent can maintain across different sectors.